2017
DOI: 10.1016/j.ijporl.2017.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Clinical role of electrocochleography in children with auditory neuropathy spectrum disorder

Abstract: OBJECTIVES To assess electrocochleography (ECochG) to tones as an instrument to account for CI speech perception outcomes in children with auditory neuropathy spectrum disorder (ANSD). MATERIALS & METHODS Children (<18 years) receiving CIs for ANSD (n=30) and non-ANSD (n=74) etiologies of hearing loss were evaluated with ECochG using tone bursts (0.25–4 kHz). The total response (TR) is the sum of spectral peaks of responses across frequencies. The compound action potential (CAP) and the auditory nerve neurop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Two studies reported the data of open-set speech perception. 34,39 Most of the children in both groups achieved openset speech perception. According to the data collected, there was no significant difference between the 2 groups in open-set speech perception (RR = 0.85, 95% CI: 0.69, 1.05; P = .142).…”
Section: Open-set Speech Perceptionmentioning
confidence: 95%
See 2 more Smart Citations
“…Two studies reported the data of open-set speech perception. 34,39 Most of the children in both groups achieved openset speech perception. According to the data collected, there was no significant difference between the 2 groups in open-set speech perception (RR = 0.85, 95% CI: 0.69, 1.05; P = .142).…”
Section: Open-set Speech Perceptionmentioning
confidence: 95%
“…Nine studies reported the data of speech recognition score. 9,19,[34][35][36][37][38]41,44 The pooled estimate showed that the speech recognition score was not significantly different between ANSD and SNHL groups (SMD = 0.01, 95% CI: −0.45, 0.47; P = .959) (Figure 2). The heterogeneity test was significant (I 2 = 84.4%, P = .001).…”
Section: Speech Recognition Scorementioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4]. The affected subjects present important speech discrimination difficulties, particularly in background noise, that are out of proportion compared to their pure-tone detection thresholds [5]. Impairments in the coding of temporal features of acoustic stimuli seem to be the main underlying mechanism responsible for these difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…(2014) showed how the composite measure known as “total response” (ECochG-TR) can predict 40% of post-CI speech variation in adult CI users. Similarly, Fontenot et al. (2017) measured ECochG-TRs and phonetically balanced kindergarten (PBK) word scores in 30 ANSD children and 74 non-ANSD children.…”
Section: Electrophysiology To Localize Pathologiesmentioning
confidence: 99%